STRATEGY FOR THE IMPLEMENTATION OF STUDENT CHARACTER EDUCATION SENIOR HIGHS SCHOOL I MARON OF PROBOLINGGO - Eva Nurdiana (LPPM STAI Muhammadiyah Probolinggo, 2021)
Strengthening character education in the Formal Education Unit is carried out by optimizing the function of the trip-center education partnership which includes schools, families, and communities. The implementation of KDP which optimizes the function of the education trip center is carried out with a class-based or integrated approach through learning activities, school culture, and the community. Research Type This research is a qualitative descriptive research type. Descriptive research is research that is intended to investigate circumstances, conditions, or other things that have been mentioned, the results of which are presented in the form of a research report. Based on the results of research and data analysis conducted by researchers regarding the strategy for implementing character education at SMAN 1 Maron, it can be concluded that the implementation of character education at SMAN 1 Maron is carried out in an integrated manner in every school activity through three main channels, namely 1) integrated through learning activities , 2) integrated through extracurricular activities, 3) integrated through cultural and habituation activities